The functional epistasis of 5-HTTLPR and BDNF Val66Met on emotion processing: a preliminary study - Outhred, Tim (Blackwell Publishing Inc, 2012)
An epistatic interaction of 5-HTTLPR and BDNF Val66Met polymorphisms has been implicated in the structure of rostral anterior cingulate cortex (rACC) and amygdala (AMY): key regions associated with emotion processing. However, a functional epistasis of 5-HTTLPR and BDNF Val66Met on overt emotion processing has yet to be determined. Twenty-eight healthy, Caucasian female participants provided saliva samples for genotyping and underwent functional magnetic resonance imaging (fMRI) during which an emotion processing protocol were presented. Confirming the validity of this protocol, we observed blood oxygen level–dependent (BOLD) activity consistent with fMRI meta-analyses on emotion processing. Region-of-interest analysis of the rACC and AMY revealed main effects of 5-HTTLPR and BDNF Val66Met, and an interaction of 5-HTTLPR and BDNF Val66Met. The effect of the BDNF Met66 allele was dependent on 5-HTTLPR alleles, such that participants with S and Met alleles had the greatest rACC and AMY activation during the presentation of emotional images relative to other genetic groupings. Increased activity in these regions was interpreted as increased reactivity to emotional stimuli, suggesting that those with S and Met alleles are more reactive to emotional stimuli relative to other groups. Although limited by a small sample, this study contributes novel and preliminary findings relating to a functional epistasis of the 5-HTTLPR and BDNF Val66Met genes in emotion processing and provides guidance on appropriate methods to determine genetic epistasis in fMRI.